Pengaruh Bimbingan Preceptorship Model Kognitif Sosial Terhadap Peningkatan Kompetensi Klinik pada Mahasiswa - Ami Tursina; Triantoro Safaria; Mujidin Mujidin (Universitas Ahmad Dahlan, 2016)
The research goal is to investigate the influence of preceptorship clinical supervision using Bandura’s social cognitive modeltoward clinical competence improvement of nursing diploma students. This research was quasi experiment using pre-posttest with control groups design. The subjects of this research were nursing diploma students who performed internship in RSJ Grhasia during 6-25 April 2015. Twenty four students which were divided into 2 groups, each of which consisted of 12 students as experimental and the rest played in control groups. Random sampling technique was used as sampling technique, the data was analyzed using independent sample T test. The results showed that preceptorship clinical supervision using Bandura’s social cognitive model improvedthe students’ clinical competence. The experiment groups’ mean of the gain score was 112 (SD±2,958), while the control group’s was 90,83 (SD±17,0,39). Thus, it can be concluded that preceptorship clinical supervision using Bandura’s social cognitive model can improve student clinical competencies compare to conventional clinical supervision method. This research can be used as a reference in developing guidance services of students through preceptorship guidance to improve clinical competence of nursing diploma students.